Metabolic syndrome study among Malay national service trainees in Kelantan - Yaacob, Najib Majdi (2010)
Metabolic syndrome is a constellation of risk factors which increases the risk for diabetes and cardiovascular diseases consisting of obesity, hypertension, hypertriglyceridemia, low level of high density lipoprotein cholesterol and hyperglycemia. As the prevalence of obesity increases, the prevalence of metabolic syndrome is also increasing at an alarming trend in numerous populations. C-reactive protein and adiponectin are two important biochemical markers which is said to have association with the development of metabolic syndrome, however the exact mechanism is not yet well understood. The objectives of this study were to describe the prevalence of metabolic syndrome among National Service trainees in Kelantan and determine the association between components of metabolic syndrome (BMI, WC, WHtR, SBP, DBP, TG, HDL-C, fasting blood glucose and fasting insulin), C-reactive protein and adiponectin levels. A cross-sectional study was conducted in 2009 involving 156 National Service trainees in Kelantan. As no single ‘gold standard’ criteria is available to diagnose metabolic syndrome in Asian adolescents, we describe the prevalence using four different criteria namely the International Diabetes Federation definition of metabolic syndrome for children and adolescents, the modified NCEP ATP III criteria for Asians, the criteria used previously in Indian adolescents population (Vikram et al., 2006) and criteria previously used in Korean adolescents population (Kim et al., 2007). Association between components of metabolic syndrome with C-reactive protein and adiponectin was studied using simple and multiple linear regression and correlation between adiponectin and C-reactive protein was studied using Pearson Correlation. The prevalence of metabolic syndrome among National Service trainees in Kelantan is 1.28% when IDF criteria and NCEP ATP III criteria was used and 0.64% when criteria by Vikram et al. and Kim et al. was used. There is significant positive linear association between C-reactive protein levels and Body Mass Index in overall, both male and female adolescents. Significant negative linear association was observed between adiponectin levels, Body Mass Index and waist to hip ratio in overall subjects. When analysis was divided according to gender, there is a significant negative association between adiponectin and Body Mass Index while in female there is a significant positive linear association between adiponectin and high density lipoprotein cholesterol. No significant correlation was found between Creactive protein and adiponectin levels. We conclude that the prevalence of metabolic syndrome among National Service trainees in Kelantan is low compared to other study population, however in view of ethnicity-related characteristics, the cut-off points used might not be suitable for our study population. Adiponectin and C-reactive protein was proven to have significant association with several components of metabolic syndrome. Further study need to be conducted to better understand the exact mechanism of metabolic syndrome especially among Malaysian adolescents.